Organizational Decision Making Behavior Under Varying Conditions of Uncertainty - Conrath, David W. (Management Science, 1967)
The problem of decision making under uncertainty generally has been treated in a rather constrained fashion. Most writers assume that the decision is to be made by an entity (the problem of utility function amalgamation is ignored), that the process whereby it is reached is of no consequence, and that an adequate definition of uncertainty is that traditionally provided in game theory. We contend, on the other hand, that these assumptions are un-realistically restrictive, and that it would do well to look at the problem in its broader aspects. A general framework is provided for this purpose, and it is used in a relatively simple example to demonstrate a possible application.